El derecho a la libertad de expresión de los adolescentes en internet y redes sociales, análisis de la sentencia 785-20-AP-22 de la Corte Constitucional Ecuatoriana - Toapanta Rosero, Edisson Fernando (2025)
The current research's title is The Right to Freedom of Expression of Adolescents on the Internet and Social Networks, an analysis of Ruling 785-20-AP-22 of the Ecuadorian Constitutional Court. Everyone has the right to freedom of thought and expression. This right includes the freedom to seek, receive, and disseminate information and ideas of all kinds, regardless of borders, whether orally, in writing, in printed or artistic form, or by any other method of your choice. Therefore, methodologically, the type of research is analytical, deductive, and explanatory. Its design was a non-experimental documentary. Therefore, the data collection technique was the interview. The instrument was the questionnaire, used in a population of 8 professionals: Judges of the Civil Unit of the city of Riobamba, judicial assistants, and lawyers in free practice, which allowed their knowledge to provide specific answers to develop the current research correctly.